The effect of different doses of rye extrudate on the digestibility of the diet feeds and biochemical parameters of rumen fluid and blood in replacement heifers - N. A. Morozkov; E. V. Sukhanova; L. S. Terentyeva (Аграрная наука Евро-Северо-Востока, 2022)
The article presents the results of identifying the effect of feeding different doses of winter rye grain extrudate on the digestibility of diet feeds and the biochemical composition of rumen fluid and blood of replacement heifers. The research was carried out at the Sokolovo dairy complex (Perm Krai). The objects of the study were replacement heifers of Holstein blackand-white breed aged 12-15 months. The concentrate part in the diet of heifers of the experimental groups consisted from winter rye grain extrudate: in the first group by 12.5 %, in the second – by 25.0 %, in the third – by 50.0 %. As the result of the research, it was revealed that the replacement heifers of the first, second and third experimental groups showed great results compared to the heifers of the control group in the digestibility of the dry matter of the diet feed by 0.63 %, 0.99 and 1.77 % (p<0.01), respectively. The ammonia content was in the rumen fluid of the first experimental group of heifers three hours after feeding by 0.62 mg% (2.97 %) p<0.05, in the second experimental group by 1.22 mg% (4.77 %) p><0.05, in the third –> ˂ 0.05, in the second experimental group by 1.22 mg% (4.77 %) p˂0.05, in the third – by 1.70 mg% (9.42 %) p˂0.01 less, compared to the control. The level of urea in the blood of heifers of the experimental groups was lower, compared with the control, in the first ‒ by 0.34 mmol/l (by 6.65 %), in the second by 0.46 mmol/l (9.21 %) and in the third – by 0.58 mmol/l (14.90 %) p˂0.05.